PENGEMBANGAN MEDIA PEMBELAJARAN GEOGRAFI BERBASIS AUGMENTED REALITY (JURNAL SPASIAL, 2021)
Learning media that uses Augmented Reality (AR) technology are able to model images in 3D that can run well. The development of Augmented Reality (AR) based learning media can make it easy for the world of education, one of which is geography. The aim of this research is to develop 3D geographic material using blender software. The method used is development research. The research model to be developed refers to the Research and Development (R&D) model with the ADDIE model (analysis, design, development, implementation, evaluation). For this research only in the analysis and design stage. The result of this research is blender software can create a 3D visual display in Augmented Reality (AR) which can help students in studying this abstract and complex material.